1999
DOI: 10.1111/j.1651-2227.1999.tb01101.x
|View full text |Cite
|
Sign up to set email alerts
|

Heart risk associated with weight loss in anorexia nervosa and eating disorders: risk factors for QTc interval prolongation and dispersion

Abstract: Swenne I, Larsson PT. Heart risk associated with weight loss in anorexia nervosa and eating disorders: risk factors for QTc interval prolongation and dispersion. Acta Paediatr 1999; 88: 304-9. Stockholm. ISSN 0803-5253Risk factors for QT c interval prolongation and dispersion, indicators of an increased risk for cardiac arrhythmia and sudden death, have been investigated in patients with eating disorders (ED) and ongoing weight loss. Patients were characterized with regard to weight, body mass index (BMI; weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
48
3
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(59 citation statements)
references
References 26 publications
7
48
3
1
Order By: Relevance
“…This finding suggests that being extremely thin or overweight is not beneficial for women with type 1 diabetes. Accordingly, a cross-sectional study in Table 2 women with eating disorders has demonstrated that low BMI is an independent predictor of QTc interval prolongation, even in the absence of electrolyte disturbances (26). In our study, the effect of both glycemic and blood pressure control appeared also more evident in women, whereas age was the strongest predictor in men.…”
Section: Results -supporting
confidence: 58%
“…This finding suggests that being extremely thin or overweight is not beneficial for women with type 1 diabetes. Accordingly, a cross-sectional study in Table 2 women with eating disorders has demonstrated that low BMI is an independent predictor of QTc interval prolongation, even in the absence of electrolyte disturbances (26). In our study, the effect of both glycemic and blood pressure control appeared also more evident in women, whereas age was the strongest predictor in men.…”
Section: Results -supporting
confidence: 58%
“…It is therefore likely that QT/RR slope is a more sensitive measure of myocardial repolarization dynamics than simply measuring absolute QT interval or changes at peak exercise. Previous studies have found BMI to be a significant predictor of QTc duration; 9 however, this correlation is not a universal finding, 32 and other studies only detect a correlation with QT dispersion and LV mass index. 47 Certainly BMI is a guide to the severity of malnutrition, although it is imperfect, and because QT duration is affected by so many factors, the association between BMI and QT may not always be readily apparent, particularly in the context of moderate or minor reductions in BMI.…”
Section: Discussionmentioning
confidence: 87%
“…10 QT prolongation may occur in AN as a consequence of electrolyte abnormalities such as hypokalemia occurring as a direct consequence of malnutrition, 7,28 but QT prolongation can occur in the absence of overt biochemical disturbance. 6,8,9 Abnormal ion transport may also occur in malnourished cells independent of absolute serum electrolyte concentrations, 29 and such abnormalities may contribute to QT prolongation in AN. Consistent with our observation of decreased LV mass in the present cohort, a variety of structural changes may occur within the myocardium of patients with AN, including myocyte autolysis and hypotrophy and an increased concentration of cellular infiltrate and fibrotic tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations